Association between subjective cognitive decline and falls in middle-aged adults. Issue 2 (17th May 2022) - Hwang, In Cheol; Ahn, Hong Yup
Abstract: Falling experiences and the fear of falling in relation to subjective cognitive decline (SCD) was examined in middle-aged Koreans. A nationwide cross-sectional study was conducted using data from the 2019 Korea Community Health Survey. The final analysis included 92, 323 individuals aged 40–64 years who had available data on SCD and falls. A multivariate regression model was applied to examine the independent effect of SCD on falls. Approximately 10.7% of participants had experienced a fall in the previous 12 months. Stepwise multivariate regression analysis showed that SCD was independently associated with a falling experience (adjusted odds ratio [95% confidence interval], 1.16 [1.53–1.70]); individuals with SCD were more likely to experience falling (13.9% vs. 9.14%, p  < 0.001) and had more fear of falling (2.33% vs. 1.74%, p  < 0.001). In conclusion, SCD is independently associated with falls in the middle-aged, which highlight the clinical need to investigate cognitive deficits among this population.